Regulation of the human erythropoietin expression via an upstream open reading frame in muscle, cardiac and neuronal tissue, and its impact in possible ischemic scenarios - Niza, Joana Martins Pinto Simas (2022)
Tese de Mestrado, Biologia Humana e Ambiente, 2022, Universidade de Lisboa, Faculdade de Ciências